2019
DOI: 10.3390/rs11040444
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage of Nepal’s Second Largest Lake (Phewa Tal) Due to Watershed Degradation and Increased Sediment Influx

Abstract: Phewa Lake is an environmental and socio-economic asset to Nepal and the city of Pokhara. However, the lake area has decreased in recent decades due to sediment influx. The rate of this decline and the areal evolution of Phewa Lake due to artificial damming and sedimentation is disputed in the literature due to the lack of a historical time series. In this paper, we present an analysis of the lake’s evolution from 1926 to 2018 and model the 50-year trajectory of shrinkage. The area of Phewa Lake expanded from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The growing population and urbanization in the catchment are causing municipal discharge, discharge from hotels/restaurants and subsurface flow from septic tanks leading to sedimentation and siltation, and water quality deterioration (Rai, 2000a;Ross and Gilbert, 1999). Based on the rate of areal decline and sediment influx, 80% storage capacity of Phewa Lake has been reported to be lost by the next 110-347 years (Watson et al, 2019). Phewa Lake is one of the better-studied lakes in the Pokhara Valley (Adhikari and Khadka, 2017;Ferro and Swar, 1978;Gurung et al, 2006;Gurung et al, 2010;Hickel, 1973;Jones et al, 1989;Kato and Hayashi, 1982;Pradhan and Kim, 2017;Rai, 2000a;Rai, 2000b;Regmi et al, 2017;Ross and Gilbert, 1999;Rowbotham and Dudycha, 1998;Swar and Fernando, 1979a;Swar and Fernando, 1979b;Swar and Fernando, 1980;Watson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The growing population and urbanization in the catchment are causing municipal discharge, discharge from hotels/restaurants and subsurface flow from septic tanks leading to sedimentation and siltation, and water quality deterioration (Rai, 2000a;Ross and Gilbert, 1999). Based on the rate of areal decline and sediment influx, 80% storage capacity of Phewa Lake has been reported to be lost by the next 110-347 years (Watson et al, 2019). Phewa Lake is one of the better-studied lakes in the Pokhara Valley (Adhikari and Khadka, 2017;Ferro and Swar, 1978;Gurung et al, 2006;Gurung et al, 2010;Hickel, 1973;Jones et al, 1989;Kato and Hayashi, 1982;Pradhan and Kim, 2017;Rai, 2000a;Rai, 2000b;Regmi et al, 2017;Ross and Gilbert, 1999;Rowbotham and Dudycha, 1998;Swar and Fernando, 1979a;Swar and Fernando, 1979b;Swar and Fernando, 1980;Watson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study also revealed a decrease in the agricultural land and an increase in forests (Rimal et al, 2018). At the same time, the lake's ecosystem has significantly changed such as an increase in mercury concentration, trace elements (Sharma et al, 2015), and sedimentation rates (Ross and Gilbert, 1999), while a decrease in the lake water quality (Rupakheti et al, 2017), and volume (Watson et al, 2019). The recent inventory of lakes and water bodies in Nepal by the Department of Forestry (DoF) in 2017 found that 95% of lakes have undergone serious transformations (DoF, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Nep J Environ Sci (2019), 7, 31-39 https://doi.org/10.3126/njes.v7i0.34473 rest of the months, the lake receives water from the tributaries and groundwater seepage (Watson et al, 2019). The lake is fed by two perennial streams: namely the Harpan Khola and Andheri Khola, as well as several other seasonal streams, and the water of the lake exits through an outlet at the Dam site area throughout the year.…”
Section: Tu-cdesmentioning
confidence: 99%